2015
DOI: 10.1021/la504952k
|View full text |Cite
|
Sign up to set email alerts
|

Multilayering of Surfactant Systems at the Air–Dilute Aqueous Solution Interface

Abstract: In the last 15 years there have been a number of observations of surfactants adsorbed at the air-water interface with structures more complicated than the expected single monolayer. These observations, mostly made by neutron or X-ray reflectivity, show structures varying from the usual monolayer to monolayer plus one or two additional bilayers to multilayer adsorption at the surface. These observations have been assembled in this article with a view to finding some common features between the very different sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 77 publications
7
44
0
Order By: Relevance
“…The structure/transport coupling paves the way toward homogeneous coatings through drying, which requires to avoid the coffee ring effect (21). It can also provide molecular explanations to numerous observations of multilayer films at the air-liquid interfaces (22)(23)(24)(25), with important consequences such as the reduction of water evaporation from water reservoirs (26) and the stabilization of foams through the buildup of multilayer surfactant films (27). To conclude, we have unveiled a homeostatic mechanism illustrating the moderation principle announced by Le Chatelier, which states that the system responds to a nonequilibrium perturbation by opposing it.…”
Section: Discussionmentioning
confidence: 99%
“…The structure/transport coupling paves the way toward homogeneous coatings through drying, which requires to avoid the coffee ring effect (21). It can also provide molecular explanations to numerous observations of multilayer films at the air-liquid interfaces (22)(23)(24)(25), with important consequences such as the reduction of water evaporation from water reservoirs (26) and the stabilization of foams through the buildup of multilayer surfactant films (27). To conclude, we have unveiled a homeostatic mechanism illustrating the moderation principle announced by Le Chatelier, which states that the system responds to a nonequilibrium perturbation by opposing it.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the traditional experimental techniques, these modern tools are capable of investigating different interfaces at molecular resolution. To name a few, the radiotracer method (Dixon et al, 1949;Aniansson et al, 1950;Matuura et al, 1959), ellipsometry (Mang et al, 1980), X-ray and neutron reflectivity Thomas et al, 2015), ion scattering spectroscopy (Andersson et al, 2014) and non-linear optical techniques, i.e. second harmonic generation (SHG) spectroscopy (Corn et al, 1994) and sum frequency generation (SFG) spectroscopy (Richmond, 2002) have already been used to determine the interfacial distribution and structure of the adsorption layers of surfactants and inorganic ions.…”
Section: Approaches To the Study Of Interfaces: The Pros And Consmentioning
confidence: 99%
“…This common view has also been adopted by the community when applying the other models such as the Langmuir isotherm to many surfactant solutions. Nonetheless, recent studies have demonstrated strong evidence for the existence of multilayers at air/liquid interfaces (Thomas et al, 2015). The monolayer adsorption assumption has recently caused an argument about the applicability of the Gibbs isotherm to the analysis of surface tension data .…”
Section: Gaps In Knowledge and Research Objectivesmentioning
confidence: 99%
See 2 more Smart Citations